Pengembangan Video Pembelajaran Berbasis Animaker pada Materi Penerapan Kimia dalam Kehidupan Sehari-hari di SMA Fase E - Sukmawati, Irma; Irhamni, Irhamni; Solfarina, Solfarina (Universitas Nusa Cendana, 2024)
Chemistry can sometimes be difficult because the teaching methods are boring, useless, and completely focused on memorization. This research aims to produce interesting animation-based learning materials about the application of chemistry in everyday life and to determine its feasibility and practicality. Animaker-based learning videos are created and packaged using Animaker.com, Microsoft PowerPoint, Canva, Genially, and Google Sites. This research uses Research & Development techniques and the ADDIE model (Analysis, Design, Development, Implementation, And Evaluation). The results of the assessment by material experts and media experts regarding the feasibility of this learning video are in the very feasible category with the average validation results obtained by material experts being 97% and 96% for media experts. Based on the assessment results, the average student response shows that every aspect of interest, material and language received a very good or very practical category, with a percentage score of 90% in the Animaker-based animated video learning media in the material Application of Chemistry in Everyday Life for class X for high school this is very practical to use.